2004
DOI: 10.1021/jp037880z
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Methane Dehydrogenation on Pt{110}(1 × 2). Part I:  Chemisorption of CHx(x= 0 −3)

Abstract: The chemisorption of methane dissociation intermediates, CH x (x = 0−3), on Pt{110}(1 × 2) has been investigated using calculations based on density functional theory. For all species considered, the most stable adsorption site identified on the missing-row reconstructed (1 × 2) surface is the site that not only completes the tetravalency of the carbon atom but also involves the maximum number of ridge Pt atoms for a site of that type. Thus, methyl (CH3) preferentially occupies the ridge atop site; methylene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 90 publications
(184 reference statements)
5
74
1
Order By: Relevance
“…The photochemical hydrogenation of methyl radical on Pt(1 1 1) has been investigated with AR-TPD [17]. More recently, the dissociative chemisorption of methane and dissociative intermediates, CH x (x = 0-3), on Pt{1 1 0}(1 · 2) has been studied extensively with molecular beam techniques [18], and DFT calculations [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The photochemical hydrogenation of methyl radical on Pt(1 1 1) has been investigated with AR-TPD [17]. More recently, the dissociative chemisorption of methane and dissociative intermediates, CH x (x = 0-3), on Pt{1 1 0}(1 · 2) has been studied extensively with molecular beam techniques [18], and DFT calculations [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…It is clear from the results that the short-bridge configuration is the most stable one. This has been also shown for another carbene species (CH 2 ), when adsorbed on different metal surfaces [53][54][55][56][57].…”
Section: Stability Of the Interaction Modes Of The Cxymentioning
confidence: 55%
“…7. King et al [57] showed a similar strong orbital interaction of the CH 2 fragment with Pt atoms at the same adsorption site on the Pt(110)(1 9 2) reconstructed surface.…”
Section: Binding Energymentioning
confidence: 87%
“…The insertion of carbon into molybdenum lattice could increase the Mo Mo distance, which would change the electron redistribution of Mo atoms in a manner, and cause the d-band contraction. Thus, Mo 2 C presents similar electronic structure to the transition metals and exhibits similar catalytic activity [44]. In this study, both phases of Mo 2 C have demonstrated high catalytic activities for ethane hydrogenolysis.…”
Section: Electronic Structure Analysismentioning
confidence: 59%